Design and fabrication of a heat exchanger for portable solar water distiller system - Abduhamed, A. J.; Adam, Nor Mariah; Hairuddin, Abdul Aziz; Kareem, H. K. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Heat exchanger H.X.s is the equipment used to transfer the thermal energy between two or more fluids at varying temperatures. The nature of this paper is an experimental study of the optimum design for shell and tube heat exchanger as a condenser with high productivity of drinking water for portable solar water distiller. The elaboration covers the aspects of considerations, design, fabrication, and test of the shell and tube H.X. as a portable condenser for solar water distiller system. The system consists of a portable stainless steel condenser, which is able to be dismantled and assembled without tools. The experimental result establishes that the condenser is able to produce 3.8 liter /hour of distilled water from vapor at 99.7 ̊C of inlet temperature and 4 liter/hour vapor flow rate, with 130 liter /hour as a condenser coolant water flow rate. The heat efficiency of the condenser can be increased by means of minimizing the tube’s thickness and vapor inlet pressure. There is no back pressure effect on the system and the pressure drop in both sides of the condenser is reportedly of very low value and negligible, therefore, no need for a pressure pump is to be eliminated.